Gender and Export Behaviour: Evidence from Women-Owned Enterprises - Welch, Catherine L. (Journal of business ethics, 2008)
This article draws on the results of a qualitative, exploratory study of 20 Australian women business owners to demonstrate how using a ‹gender as social identity’ lens provides new insights into the influence of gender on exporting and entrepreneurial behaviour. Interview data reveal perceptions of gender identity and gender relations varied and influenced the interpretations which women business owners placed on their exporting activities. Women in the study used different terms to describe exporter and entrepreneurial characteristics to those found in extant literature. A strong theme was exporting as a life-changing experience that allowed the women to grow personally as well as grow the business and succeed as exporters.